Combined hydrous ferric oxide and quaternary ammonium surfactant tailoring of granular activated carbon for concurrent arsenate and perchlorate removal - Jang, M.; Cannon, F.S.; Parette, R.B.; Yoon, S.J.; Chen, W. (2009)
Activated carbon was tailored with both iron and quaternary ammonium surfactants so as to concurrently remove both arsenate and perchlorate from groundwater. The iron (hydr)oxide preferentially removed the arsenate oxyanion but not perchlorate; while the quaternary ammonium preferentially removed the perchlorate oxyanion, but not the arsenate. The co-sorption of two anionic oxyanions via distinct mechanisms has yielded intriguing phenomena. Rapid small-scale column tests (RSSCTs) with these dually prepared media employed synthetic waters that were concurrently spiked with arsenate and perchlorate; and these trial results showed that the quaternary ammonium surfactants enhanced arsenate removal bed life by 25-50 when compared to activated carbon media that had been preloaded merely with iron (hydr)oxide; and the surfactant also enhanced the diffusion rate of arsenate per the Donnan effect. The authors also employed natural groundwater from Rutland, MA which contained 60 Î¼g/L As and traces of silica, and sulfate; and the authors spiked this with 40 Î¼g/L perchlorate. When processing this water, activated carbon that had been tailored with iron and cationic surfactant could treat 12,500 bed volumes before 10 Î¼g/L arsenic breakthrough, and 4500 bed volumes before 6 Î¼g/L perchlorate breakthrough. Although the quaternary ammonium surfactants exhibited only a slight capacity for removing arsenate, these surfactants did facilitate a more favorably positively charged avenue for the arsenate to diffuse through the media to the iron sorption site (i.e. via the Donnan effect).